Pendidikan Islam Berbasis Adab Dalam Kitab Ta’lim Al-Muta’allim dan Relevansinya terhadap Pendidikan Karakter Kontemporer - Khairul Abdillah Harahap; Nelly Setia Wati (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
This study examines the concept of Islamic education as articulated by Imam al-Zarnuji in Ta’lim al-Muta’allim and analyzes its relevance to contemporary Islamic education. The purpose of this study is to systematically map educational goals, the roles of teachers and students, and the ethical foundations of learning formulated by al-Zarnuji in response to moral and character-related challenges in modern education. This research employs a qualitative descriptive approach with a library research design. Primary data are derived from Ta’lim al-Muta’allim, while secondary data are obtained from various scholarly works on Islamic education and character education, which are analyzed using content analysis techniques.The findings indicate that al-Zarnuji conceptualizes education as a holistic process oriented toward moral development, spiritual closeness to Allah, and the social usefulness of knowledge. Knowledge is understood not as an end in itself, but as a means of worship that must be grounded in sincere intention and proper conduct (adab). Students are positioned as active moral agents who are required to cultivate perseverance and self-discipline, whereas teachers are regarded as primary moral exemplars whose authority is rooted in ethical and spiritual integrity. Learning ethics such as sincerity, respect for knowledge and teachers, and consistency constitute the foundation of educational success. This study affirms the continued relevance of al-Zarnuji’s educational thought for strengthening character education within contemporary Islamic education.